Rape by Blood Relatives: A Study of Children as Subjects of Sexual Assault - Machmud, Hadi; Abidin, Azwar; Alim, Nur; Fatimah Kadir, St.; Yahya Obaid, Moh. (KnE Social Sciences, 2022)
This study’s focus was children as the subjects of sexual assault by blood relatives, commonly known as incest, in Kendari city. The main questions were: 1) what were the modus operandi of these blood relatives in committing the sexual assault; 2) what were the physical and psychological impacts inflicted on the victims; and 3) what were the treatments given by the authorities in an attempt to rehabilitate the victims from post-accident trauma? The data were collected through interviews, observations and document analysis. The findings indicated that these blood relatives committed the sexual assault based on the following modus operandi: isolating the victim from the neighbourhood, taking the victim on a trip, threatening the victim with killing or beating, teasing the victim by offering something desirable, or poisoning the victim with drugs. The physical impacts inflicted on the victims were vaginal infections with pus and blood streaming from the lesion, dysfunctions of the reproductive organs, high-risk pregnancy, lacking in vitality, and paleness. Regarding the psychological impacts, the victims suffered from post-accident trauma by living in a constant fear and avoiding contact with people, isolating themselves from the crowd, social damnation and excommunication that led to internal disharmony in the family or parental divorce. The authorities, led by The Woman Empowerment and Children Protection Service, attempted immediate rehabilitation of the victims by working in cooperation with third parties such as civil society organizations and psychologists to provide basic needs, counsel the neighbourhood where the victims live to support and foster the rehabilitation, as well as educate them that such a tragedy should not justify social damnation upon the victims and their families. Keywords: rape, blood relatives, sexual assault, children